The impact of postmodernist culture on the Malay youth lifestyles : the case of Black Metal music in Malaysia - Nor Hayati Mohd Redzwan (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
About three years ago, there were reports about an anti-establishment and antireligious cult in the northern states of Malaysia which specifically targets teenagers. This cult is identified as the “Black Metal music group.” The Black Metal ideology, which is one of the genres in popular music, is formed on a basic idea of straightforward anti-religion and disbelief in inherent values to existence or society. Popular music, including the Black Metal music, comes from a world-wide subculture which is valued as a postmodern influence. Therefore, the Malays are approaching a postmodern era which will begin to shape their lives. Realizing what has happened, the issue of Black Metal music which confronts the Malay youths has traumatized and surprised the public at all levels. With Black Metal music, it is assumed that the Malay youths have been exposed to the storm of postmodernism. Indeed, this influential phenomenon is not only diminishing the Malay Muslim lifestyle, but it also destroys their faith, with or without their consciousness. Thus, this research is an attempt to present the conception of modernity and postmodernism in modern Malay society. It also gives a clear depiction of what Black Metal music issue is all about. The objective is to analyze which mode of postmodernism has influenced the Malay society, particularly how it shapes the young Malay youths' lifestyle and more specifically, to identify the impact of Black Metal on Malay youths' akhlāq. This research utilized both library research and field work where references comprised of books, journals and interviews.